Teacher orientation of Adiwiyata School trustees in environment character building in Malang Senior High School, Indonesia - Sukarsono Sukarsono; Lise Chamisijatin; Eko Susetyorini (Journal of Social Studies (JSS), 2021)
This study was conducted to determine the orientation of teachers builder Adiwiyata school program, a program of the Ministry of Environment together with the Ministry of Education which aims to create good conditions for schools to be a place of learning and awareness of the school community so that in the future the school community can be partly responsible for the efforts to save the environment and sustainable development. This study is a phenomenological qualitative study conducted on teachers' School Trustees Adiwiyata Program Malang. High School who has been awarded the highest Adiwiyata (gold) from the government as an independent school Adiwiyata school used as study sites. Data were collected using in-depth interview techniques (in-depth interviews) and study documentation. Analysis of data using triangulation techniques performed simultaneously including data collection, data reduction, data presentation, verification, and conclusion. The study found that teachers Adiwiyata Trustees have had a clear orientation which is based on the activity or better known as professional orientation. Orientation is systematically arranged sequentially from the most fundamental orientation to the orientation of the peak to be reached as follows: policy development orientation, the orientation of the increased insight, orientation awareness, orientation awareness-raising, and conservation orientation. Conservation orientation is the direction that was built to accomplish a character loving environment. Orientation conservation in many ways shows that teachers and students have the character of a good conservationist. Another orientation is an additional orientation and done outside the main orientation if the main orientation has been reached.